2023
DOI: 10.1186/s13690-023-01154-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in leukemia outcomes based on health care expenditures using estimates from the GLOBOCAN 2020

Maedeh Amini,
Rajesh Sharma,
Chinmay Jani

Abstract: Background Leukemia contributes significantly to the global cancer burden. Due to the importance of evaluating improvements in leukemia outcomes, the current study aimed to examine the variations in mortality-to-incidence ratio (MIR) between genders and association of MIR with the health expenditures in selected countries. Methods The leukemia incidence and mortality rates were extracted from the GLOBOCAN 2020 database. In total, 56 countries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…The global age-standardized rate of incidence was 5.4 per 100,000 and there was an almost five-fold variation worldwide. Globally, the frequency of new cases and deaths is more marked among males compared to females (269,503 vs. 205,016; 177,818 vs. 133,776, respectively) [4]. Moreover, it was found that countries with higher income levels had a higher incidence of 1.5 times higher than low-income countries [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global age-standardized rate of incidence was 5.4 per 100,000 and there was an almost five-fold variation worldwide. Globally, the frequency of new cases and deaths is more marked among males compared to females (269,503 vs. 205,016; 177,818 vs. 133,776, respectively) [4]. Moreover, it was found that countries with higher income levels had a higher incidence of 1.5 times higher than low-income countries [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that countries with higher income levels had a higher incidence of 1.5 times higher than low-income countries [6]. GLOBOCAN 2020 estimated that leukemia was the 15th most frequently diagnosed cancer worldwide and it is ranked as the 11th leading cause of cancer-related mortality, accounting for about 4.7% of all cancer-related deaths [4,7]. Pathophysiological, leukemia occurs due to the malignant transformation of pluripotent hematopoietic stem cells (both myeloid and lymphoid precursors).…”
Section: Introductionmentioning
confidence: 99%
“…Between ten and 20 lakh new cases of colorectal cancer (CRC) are diagnosed each year, making it one of the most prevalent cancers in the world. With over 700,000 cancer-related deaths each year, only lung, liver, and stomach cancers contribute to most of these cases [ 6 ]. CRC is the second most prevalent cancer among women (9.2%) and males (10%), respectively.…”
Section: Introductionmentioning
confidence: 99%